PERAN PENGURUS MAJELSI TAKLIM NURUL YAQIN DALAM MENGEMBANGKAN KARAKTER RELIGIUS REMAJA MASJID DI SINGKAWANG TENGAH - Wella Safira; Rustiyarso Rustiyarso; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstrackThis study aims to determine the Role of the Taklim Council Management Nurul Yaqinin Developing Youth Religious Characters in Central Singkawang. The researchmethod used is descriptive with a qualitative research form. The data source of thisresearch is the Management and Youth of Majelis Taklim Nurul Yaqin. Data collectiontechniques in this study were through observation, interviews, and documentation,while the data collection tools used were observation guides, interview guides, andnotebooks and archives. The analysis in this study was presented in a descriptivequalitative manner using 8 informants consisting of the Chairperson of the TaklimCouncil Nurul Yaqin, Cadre Staff, and 6 Adolescent Members. The results of this studyindicate that the Role of the Council Management in developing the religiouscharacterof adolescents through exemplary, habituation, advice, and supervision.Although not all members participated in the activities provided by the board, otheryouth members participated in activities such as congregational prayer, recitation,mutual cooperation, and other social activities.Keywords: Youth, Religious Character, Role of Management, Majelis Taklim.